Calcium channel blockade attenuates abnormal synaptic transmission in the dentate gyrus elicited by entorhinal amyloidopathy. Issue 10 (7th July 2016) - Gholami Pourbadie, Hamid; Naderi, Nima; Janahmadi, Mahyar; Mehranfard, Nasrin; Motamedi, Fereshteh
Abstract: Entorhinal‐hippocampal network is one of the earliest circuits which is affected by Alzheimer's disease (AD). There are numerous data providing the evidence of synaptic deficit in the dentate gyrus (DG) of AD animal model. However, there is little known about how entorhinal cortex (EC) amyloidophaty affects each excitatory and/or inhibitory transmission in the early stage of AD. On the other hand, it is believed that calcium dyshomeostasis has a critical role in the etiology of AD. Here, the effect of the EC amyloid pathogenesis on excitatory or inhibitory post synaptic currents (EPSC and IPSC, respectively) in the DG granule cells and then the possible neuroprotective action of L‐type calcium channel blockers (CCBs), nimodipine and isradipine, were examined. The amyloid beta (Aβ) 1–42 was injected bilaterally into the EC of male rats and one week later, synaptic currents in the DG granule cells were assessed by whole cell patch clamp. EPSCs were evoked by stimulating the perforant pathway. Voltage clamp recording showed profound decrease of evoked EPSC amplitude and paired pulse facilitation in the DG granule cells of Aβ treated rats. Furthermore, AMPA/NMDA ratio was significantly decreased in the Aβ treated animals. On the other hand, amplitude of IPSC currents was significantly increased in the DG granule cells of these animals. These modifications of synaptic currents were partially reversed by daily intracerebroventricular administration of isradipine or nimodipine. In conclusion, our results suggest that Aβ in the EC triggers decreased excitatory transmission in the DG with substantial decrement in AMPA currents, leading to a prominent activity of inhibitory circuits and increased inhibition of granule cells which may contribute to the development of AD‐related neurological deficits in AD and treatment by CCBs could preserve normal synaptic transmission against Aβ toxicity. Abstract : Using whole‐cell patch clamp, the authors show that entorhinal amyloidopathy triggers a decreased excitatory transmission and paired pulse facilitation in the dentate gyrus (DG), leading to a prominent activity of inhibitory circuits and increased inhibition of granule cells which may contribute to the development of Alzheimer's disease (AD)‐related neurological deficits in AD. Treatment by calcium channel blockers (CCBs) could preserve normal synaptic transmission against Aβ toxicity. The entorhinal and DG granular cells both send excitatory collateral to inhibitory hilar cells which in turn inhibits DG granule cells by GABA transmission.